Water Resources Management in Vulnerable Ecosystems: Quiroz River Basin, Piura - Tostes, Marta; Espejo, Mirian; Macedo, Enrique; Torres, Fidel (European Journal of Sustainable Development, 2020)
According to the IPCC (2014), access to water resources is increasingly limited due to the effects of climate change; in consequence, vulnerability of ecosystems and their inhabitants increases. Thus, it is necessary to develop socio-organizational capacities to mitigate and adapt to this scenario, where retribution mechanisms for ecosystem services (MRSE for its Spanish acronym) become more relevant. The research attempts to analyze the coordination among agents involved in sustainable water resources management, to face climate change vulnerability in high biodiversity areas. For this purpose, the implementation of the Quiroz-Chira water fund will be studied as a case that generates institutionalism for sustainability of this mechanism and that represents an important social innovation that can be replicated. The methodology has a descriptive scope and applies qualitative techniques that complement secondary sources systematized with WebQDA software. Results indicate high vulnerability of the analyzed basin districts and a correct governance in this innovation, both with a sustainable development approach oriented to conservation of water potential. This implies good articulation for implementation of the MRSE and promotion of interests’ unification between contributors and water resources retributive entities. Keywords: Climate change, Sustainable development, Watershed, Governance, Ecosystem services